Farnesyl Transferase Inhibitor Lonafarnib Enhances α7nAChR Expression Through Inhibiting DNA Methylation of CHRNA7 and Increases α7nAChR Membrane Trafficking - Chen, Tingting; Cai, Chengyun; Wang, Lifeng; Li, Shixin; Chen, Ling (Frontiers in Pharmacology, 2020)
Inhibition of Ras farnesylation in acute has been found to upregulate α7 nicotinic acetylcholine receptor (α7nAChR) activity. This study was to investigate the effect of chronic administration for 7 days of farnesyl transferase inhibitor Lonafarnib (50 mg/kg, intraperitoneally injected) to male mice on the expression and activity of α7nAChR in hippocampal CA1 pyramidal cells. Herein, we show that Lonafarnib dose-dependently enhances the amplitude of ACh-evoked inward currents (IACh), owning to the increased α7nAChR expression and membrane trafficking. Lonafarnib inhibited the phosphorylation of c-Jun and JNK, which was related to the DNA methylation. In addition, reduced DNA methyltransferase 1 (DNMT1) expression was observed in Lonafarnib treated mice, which was reversed by JNK activator. Lonafarnib upregulated expression of α7nAChR was mimicked by DNMT inhibitor, and repressed by JNK activator. However, only inhibited DNA methylation did not affect the IACh, and the JNK activator partially decreased the Lonafarnib upregulated IACh. On the other hand, Lonafarnib also increased the membrane expression of α7nAChR, which was partially inhibited by JNK activator or CaMKII inhibitor, without changes in the α7nAChR phosphorylation. CaMKII inhibitor had no effect on the expression of α7nAChR. Lonafarnib enhanced spatial memory of mice was also partially blocked by JNK activator or CaMKII inhibitor. These results suggest that Ras inhibition increases α7nAChR expression through depressed DNA methylation of CHRNA7 via Ras-c-Jun-JNK pathway; increases the membrane expression of α7nAChR resulting in part from the enhanced CaMKII pathway and total expression of this receptor, consequently enhances the spatial memory.